Lei geral de proteção de dados: adequações dos serviços odontológicos no Brasil - Lima, Manoel Pereira de (2023)
Introduction: The General Data Protection Law (GDPL), 13.709/2018, in force since 2020, deals with the management and protection of personal data by companies, public agencies and individuals in Brazil, aiming to guarantee the right to freedom and privacy. In health, as well as in other sectors, the processing of patients' personal data must occur with the consent of the holder and in accordance with the new law. Objective: To verify and understand the security in the management of personal data by clinics and dental offices in Brazil, regarding the adaptations to the GDPL. Methods: Methodology: This is a cross-sectional study, approved by the Ethics and Research Committee - ERC (CAAE: 60717822.4.0000.5188), made available to dentists throughout the country through the Google Forms platform, through a structured questionnaire. A sample size of 374 dentists was defined, through the calculation carried out on the online platform OpenEpi (https://www.openepi.com/), adopting a 95% confidence interval and the design effect (deff) of 2.0. After obtained, the data were exported and tabulated in an Excel spreadsheet, and submitted for analysis in the IBM SPSS®️ software (25.0, IBM Corporation, Armonk, New York, USA). Descriptive and exploratory analysis was initially carried out to determine absolute and relative frequencies. Then, statistically significant associations were evaluated using the chi-square test. Results: 512 responses to the questionnaire were obtained, showing that 63.1% (n=323) of professionals are linked only to the private network. About 86% (n=441) claimed to know what personal data is, but 71.5% (n=366) cannot distinguish their difference between sensitive personal data. The improper collection of personal data of minors was observed in 16.5% of the responses obtained and 40.9% of professionals reported making some term of consent available to parents and/or guardians. About the data security mechanisms, 72.1% reported that the service was unprotected, not meeting GDPL standards and with risks of failure and information leakage. It was also observed that 54.8% of dentists use some social network to share images of patients, with WhatsApp being the largest of them (32%). Approximately 68% use access to reports and radiographic images, through the clinic's website (28%), Idoc 49.9% and Cfaz.net (5%). Statistically significant associations (p=<0.05) were observed in twelve of the questions asked, when associated with the administrative sphere. Conclusion: With the realization of the study it was possible to observe that most dentists know little about the existence of the GDPL and its applicability within dentistry, that most services lack measures for the protection of data and personal information, in addition to demonstrating the importance of the law for society, especially health-related services.